Evaluation of Serum Ferritin Status in Patients with Chronic Kidney Disease: A Cross-Sectional Study - Najla Elyounsi,; Mohamed Abuagela,; Ream Eswaiah,; Ayatullah Daw,; Hana Bakar, (AlQalam Journal of Medical and Applied Sciences, 2025)
Serum ferritin levels are a key marker for assessing iron status, but various factors, including age, can influence them. In individuals with chronic kidney disease (CKD), serum ferritin levels may be altered due to factors such as inflammation, impaired kidney function, and disease severity. Elevated ferritin levels in CKD patients can reflect both iron overload and increased inflammation, complicating the interpretation of iron status. The goal of this study was to investigate the distribution of serum ferritin levels in individuals with chronic kidney disease (CKD) and to compare them with those of healthy controls. A case-control design involving 100 participants, including 80 individuals with chronic kidney disease (CKD) as the case group and 20 healthy individuals as the control group. Serum ferritin levels were measured for all participants using standardized laboratory techniques. Data analysis was conducted using SPSS version 25, and independent t-tests were performed to compare the mean serum ferritin levels between the CKD and control groups. Serum ferritin levels were significantly higher in the case group (202.0 ± 217.5) compared to the control group (79.1 ± 72.8), with a p-value of 0.000. However, there was no significant difference in ferritin levels between male and female participants in the case group (p = 0.480). This study demonstrated that serum ferritin levels were significantly higher in individuals with chronic kidney disease (CKD) compared to healthy controls. Although there were differences in age and gender distributions between the groups, gender did not have a significant effect on ferritin levels within the CKD group. The results suggest that CKD-related factors, such as inflammation and impaired kidney function, have a more substantial impact on serum ferritin levels than gender.